Latihan Yoga Terhadap Penurunan Nyeri Haid - Eprilia Eprilia; Dahliana Dahliana; Rike Puspasari (Pusat Unggulan IPTEK, Poltekkes Kemenkes Palembang, 2021)
Dysmenorrhea is a pain that is felt during menstruation that is casually characterized by a feeling of cramps that are centered on the lower abdomen. Prevalence dysmenorrhea in Indonesia in 2008 that is 64,25%. Yoga is believed to reduce the fluid that accumulates in the back causing pain during menstruation. This research is aimed to find out the effect of yoga on the level of dysmenorrhea on the female midwifery student in STIKES Aisyiyah Palembang. This research was an quantitative study with quasy experiment design that is use one group pretest posttest design. Samples of this research were female midwifery students in STIKES Aisyiyah Palembang that felt dismenore wich met the criterias for participation. Sampling in this research using quota sampling technique.From 30 respondents, before intervention 13 respondents feel menstruation pain with mild pain scale, after intervention all respondents no longer felt dysmenorrhea (100,0%), while 17 respondents feel dysmenorrhea with moderate pain scale before intervention, after intervention 6 respondents no longer felt dysmenorrhea (35,3%), 8 respondents felt dysmenorrhea with mild pain scale (47,1%), and 3 respondents still feel dysmenorrhea with moderate pain scale (17,6%). Wilcoxon test results based on the statistical results table obtained p value of 0.000 which means that there are significant influence felt by respondents after the yoga. Yoga movements can stimulate the body to release endogenous opioids (compounds that work to inhibit pain) so that we felt painless.Yoga have an influence on the decrease of menstual pain.For further research is expected to conduct research on the effect of yoga on the reduction of dysmenorrhea by using a pure experimental design.